2022
DOI: 10.1007/s11191-021-00310-2
|View full text |Cite
|
Sign up to set email alerts
|

STEM Problem Solving: Inquiry, Concepts, and Reasoning

Abstract: Balancing disciplinary knowledge and practical reasoning in problem solving is needed for meaningful learning. In STEM problem solving, science subject matter with associated practices often appears distant to learners due to its abstract nature. Consequently, learners experience difficulties making meaningful connections between science and their daily experiences. Applying Dewey’s idea of practical and science inquiry and Bereiter’s idea of referent-centred and problem-centred knowledge, we examine how integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…According to socio-meter theory, self-esteem reflects social connection and fosters positive social support which produces higher self-esteem (Li et al, 2018 ). Social support enables the LB individuals to socialize with others which enhances the self-esteem of these children (Tan et al, 2022 ). A study conducted by Jin and Zhu ( 2022 ) examined how perceived social support is related to self-esteem, and showed that these constructs have a positive relationship.…”
Section: Review Of Literature and Hypotheses Developmentmentioning
confidence: 99%
“…According to socio-meter theory, self-esteem reflects social connection and fosters positive social support which produces higher self-esteem (Li et al, 2018 ). Social support enables the LB individuals to socialize with others which enhances the self-esteem of these children (Tan et al, 2022 ). A study conducted by Jin and Zhu ( 2022 ) examined how perceived social support is related to self-esteem, and showed that these constructs have a positive relationship.…”
Section: Review Of Literature and Hypotheses Developmentmentioning
confidence: 99%
“…The concept of problem-solving gets the skills needed to collect and implement the information that was found on the internet ( Lin et al, 2021 ). Within M-learning inquiry learning students come across different kinds of problems that can be solved from information over the internet ( Tan et al, 2022 ). The students with an inquiry learning style can develop problem-solving skills because such students engage in data collection from various sources to find the most appropriate and accurate solution to the problem ( Sejati et al, 2021 ).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…• The CDIO approach and CT are discussed separately, thus their relation and interactions are ignored. For example, Sanford and Naidu [33] considered the relation of mathematical modeling and CT; Qian and Choi [28] studied the process of developing abstraction in CT; Tan et al [37] discussed the balancing disciplinary knowledge and practical reasoning in problem solving; Nadelson et al [25] exhibited the STEM spectrum in K12 education. Juškevičienė et al [13] presented the design process of the strategy for CT abilities development in basic school.…”
Section: Introductionmentioning
confidence: 99%
“…The CT integrates three kinds of thinking methods into a novel method, which includes the general mathematical thinking method used for problem solving, the general engineering thinking method for the design and evaluation of huge and complex systems in the real world, and the general scientific thinking method for understanding complexity, intelligence, psychology, and human behavior.Although STEM education, the CDIO approach, and the CT are hot topics and there are quite a number of contributions dealing with them in recent decades, there are still some deficiencies: The CDIO approach and CT are discussed separately, thus their relation and interactions are ignored. For example, Sanford and Naidu [33] considered the relation of mathematical modeling and CT; Qian and Choi [28] studied the process of developing abstraction in CT; Tan et al [37] discussed the balancing disciplinary knowledge and practical reasoning in problem solving; Nadelson et al [25] exhibited the STEM spectrum in K12 education. Juškevičienė et al [13] presented the design process of the strategy for CT abilities development in basic school.…”
Section: Introductionmentioning
confidence: 99%